Stability Indicating Method Development and Validation for Assay of Omeprazole Sodium for Injection by a Rapid RP-HPLC - Dande, Aishwarya; Reddy, Gummadi Rishitha; Saithya, Gaddam Saithya (Asian Journal of Pharmaceutical Research and Development, 2021)
Omeprazole,13 a member of proton pump inhibitor, used for the treatment of peptic ulcers, it supresses gastric acid secretion by inhibiting H+/K+ ATPase. A new fundamental, rapid and sensitive HPLC method was developed for the assay of Omeprazole sodium for injection. It was validated according to ICH and FDA guidelines 2. The HPLC analysis was performed on Dionex ultimate 3000 system equipped with C-18 (150cm*4.6mm) 5µ column, with a mixture of ammonium acetate and acetonitrile buffer in the ratio 65:35 v/v as the mobile phase at the wavelength (λ) 305nm. The total run time was 8 minutes. The calibration curve was linear for 50-150% range of the analytical concentration of 40mg/ml, r2 was found to be 0.9998. The precision was calculated and % RSD was 0.1 % and the recovery of omeprazole was within the range of 98-102%. Validation parameters like robustness, solution stability studies, specificity and forced degradation studies were performed and found to be within acceptance limits. As compared to other methods, this method was found to be more accurate, linear, precise and specific, with short run time. All the results were acceptable and confirmed that the method is suitable for its intended use in routine quality control analysis.